Holman in South - Unknown (Newsday)
Composer, arranger and player Ray Holman made an appearance at Jazz Sundays at 110 Jazz and Calypso Lounge. Holman along with friends Lancelot Nicholls (guitar), Joey Samuel (drums), Michael Jermain (bass), Errol Ramah (percussions) and Mark Brewster (flute) played music for the season including local parang, standard Jazz classics as well as songs by Kitchener, Sparrow and Lord Blakie.
Keywords: Steel bands (Music) -- Trinidad and Tobago; Holman, Roy; Arrangers (Musicians) -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago